Pengaruh Lokasi dan Kelengkapan Produk Terhadap Keputusan Pembelian Konsumen di toko Sehati Jaya - Nasution, Elda Marina; Aramita, Finta (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2024)
This research aims to determine the influence of location and product completeness on consumer purchasing decisions at UD stores. Sehati Jaya. This type of research is quantitative. The data used is questionnaire data and analysis using SPSS 25. The population in this research is UD Shop visitors. Sehati Jaya. The sampling technique used is non-probability sampling and accidental sampling using the hair formula because the population is not yet known with certainty and suggests that the minimum sample size be 5-10 times the indicator variable. Based on the results of this research, it shows that partially the influence of location (X1) has a positive and significant effect on consumer purchasing decisions at UD stores. Sehati Jaya. The influence of product completeness (X2) has a positive and significant effect on consumer purchasing decisions at UD stores. Sehati Jaya.